An organic Schottky diode (OSD) based on a-silicon/polycarbazole contact - Srivastava A.; Chakrabarti P. (My University, 2025)
In this paper a novel organic Schottky diode (OSD) based on polycarbazole is proposed. The article presents fabrication and experimental characterization of an amorphous silicon/polycarbazole organic Schottky diode, particularly with configuration a-Si/p-PCz/ITO, wherein in the said novel Schottky diode amorphous silicon (a-Si) contact has been used in place of conventional metal contact on the semiconducting polymer to form a rectifying contact. The characterization of polymer film was done in terms of morphology, absorbance versus wavelength, bandgap and thickness. I-V measurement was performed by Semiconductor Device Analyzer. The electrical parameters such as barrier height, ideality factor, rectification ratio and reverse saturation current as extracted from I-V characteristics of the device were found to be much better than those reported earlier for Schottky diodes based on polycarbazole. The proposed organic Schottky diode (OSD) exhibits a very low dark current (∼10-14 A) and is therefore expected to have great commercial applications.